PENGARUH EKUITAS MEREK DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI SEPEDA MOTOR NMAX DI KOTA BIMA - Riska Afriani; Sri Ernawati (Lembaga Pengembangan Kinerja Dosen, 2022)
A person's consideration in buying a product is certainly inseparable from their assessment of a product they want whether it is in accordance with the consumer's value standards or not and how the value and image given by the product to potential customers is good or bad. This study aims to determine and analyze the effect of brand equity and brand image on consumer decisions in buying NMAX motorcycles in Bima City. This type of research is associative with quantitative data types from primary data sources. The research instrument used was a questionnaire with a Likert scale. Data collection techniques using observation, questionnaires and literature study. The data analysis technique uses validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results of the study show that brand equity and brand image together have a significant effect on consumer decisions in buying NMAX motorcycles in Bima City.